Improving quality of life for women with incurable fistula in Uganda - Tripathi, Vandana; Emasu, Alice; Arnoff, Elly; Mukisa, Rose; Kanakulya, Hassan; Kirya, Fred (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To understand whether reintegration services can improve quality of life (QoL) for women with incurable fistula (WIF) in Uganda.Methods: Standardized tools measuring health/psychosocial status and QoL were administered before and after intervention to assess impacts: Self-Reporting Questionnaire (SRQ-20), WHO QoL-BREF, and modified King’s Health Questionnaire (KHQ).Results: Before intervention, all participants had SRQ-20 scores >8, indicating psychological distress. After intervention, there was significant reduction (to 37%) in the proportion of participants with scores indicating distress (p=0.0003). As measured by WHO QoL-BREF, self-reported QoL and health satisfaction improved significantly after intervention (p=0.0003 and p